(3TQM QSGdI GHf CHj RjO GdbjQhGfis - (3CHi GdaVd bGSe Hf YjSi Hf fGLi GdJfhNi GdbjQhGfis; (3YHO Gddg Hf CHj RjO , YHO Gddg Hf YHO GdQMef GdfZRj GdbjQhGfj, CHh eMeO,J (B386 (3g` s
(3BNQgG (B:s
(3CSFdI hGLhHI haJGhi dHYV abgGA GdeGdcjI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B73s
Keywords: (3Gdabg GdeGdcjs